High power tapered lasers with optimized photonic crystal structure for low divergence and high efficiency. (19th March 2018) - Ma, Xiaolong; Qu, Hongwei; Qi, Aiyi; Zhou, Xuyan; Ma, Pijie; Liu, Anjin; Zheng, Wanhua
Abstract: High power tapered lasers are designed and fabricated. A one-dimensional photonic crystal structure in the vertical direction is adopted to narrow the far field divergence. The thickness of the defect layer and the photonic crystal layers are optimized by analyzing the optical field theoretically. For tapered lasers, the continuous-wave power is 7.3 W and the pulsed power is 17 W. A maximum wall-plug efficiency of 46% under continuous-wave operation and 49.3% in pulsed mode are obtained. The beam divergences are around 11° and 6° for the vertical and lateral directions, respectively. High beam qualities are also obtained with a vertical M 2 value of 1.78 and a lateral M 2 value of 1.62. As the current increases, the lateral M 2 value increases gradually while the vertical M 2 value remains around 2.